Financiranje projektov in inovacij v pametnih občinah - Jankovič, Patricija (Public Administration & Management, 2015)
The present book provides a concise overview of relevant studies in the field of financing sustainable development in communities, innovation and public private partnership, with special stress on analogy between smart cities and smart municipalities. The research generated till now the most the complete and entire repository of data connected to project financing in municipalities, the number and competences of clerks, innovation and public private partnership in Slovenian municipalities in years 2005 till 2012. It scopes one quarter of municipalities and one fifth of Slovenian population. In total of 200 hypotheses were tested for significance of number or shares of projects with different ways of financing with influential factors such as region, the number of clerks, the number of competent and high educated clerks, municipal experiences with public private partnership, cooperation between municipalities and experiences with innovation. The hypotheses were tested for each year. Effects of selected factors in the period often vary from year to year. We have explained the possible causes for the difference in power factor.